Application of PSO for optimal coordination of directional over-current relays in distribution system with distributed renewable energy sources - Lazhar Bougouffa; Abdelaziz Chaghi (Institute of Advanced Engineering and Science, 2021)
The use of distributed renewable energy sources (D-RES) in the electrical network has expanded greatly. However, integration of these resources into distribution systems caused more problems in protection related issues such as mis-coordination and changes the direction and value of fault currents. When connecting new D-RES to electrical power distribution networks, it is required to re-coordinate directional over-current relays (DOCR) to ensure the continuity of the power transmission when the short circuits take place. This work presented a particle swarm optimization (PSO) algorithm to determine two independent variables called pickup current (Ip) and time dial setting (TDS) for optimal setting of relays. From analysis result, the impacts of RES location in the distribution system on DOCRs had been observed on the optimal relays settings.